2018
DOI: 10.1523/jneurosci.0323-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Inhibition of Primary Nociceptive Signals to Dorsal Horn Lamina I Neurons by Dopamine

Abstract: The dorsal horn of the spinal cord represents the first relay station in the pain pathway where primary nociceptive inputs are modulated by local circuits and by descending signals before being relayed to supraspinal nuclei. To determine whether dopamine can modulate primary nociceptive Aδ- and C-fiber signals, the effects of dopamine were tested on the excitatory postsynaptic currents (EPSCs) recorded from large lamina I neurons and from retrograde-labeled spinoparabrachial lamina I neurons upon stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…Five of the genes in Table 5 are involved in the cocaine addiction pathway. Based on experimental studies and some indirect clinical evidence, dopamine has been suggested to have anti-nociceptive effect 4042. Cocaine increases the level of dopamine and cocaine addiction is related to pain 43.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the genes in Table 5 are involved in the cocaine addiction pathway. Based on experimental studies and some indirect clinical evidence, dopamine has been suggested to have anti-nociceptive effect 4042. Cocaine increases the level of dopamine and cocaine addiction is related to pain 43.…”
Section: Discussionmentioning
confidence: 99%
“…The final element identified in the original gate control theory is “central control,” where signals arising from the brain itself descend and modify spinal dorsal horn activity. Indeed, several brain structures are now well-established sources of descending input to the spinal dorsal horn ( Suzuki et al, 2004 ; François et al, 2017 ; Lu et al, 2018 ). They have the capacity to facilitate or inhibit dorsal horn circuits and alter the gain of pain signaling in this region.…”
Section: Role Of Pns In Pain Signalingmentioning
confidence: 99%
“…These data suggest that activation of spinal D1 and D5 receptors participates in the antiallodynic effect. Since these are stimulatory receptors, activation of D1-like receptors should lead to a pronociceptive effect [12,25]. However, there is evidence that spinal activation of D1-like receptors by low concentrations of DA depresses ventral root potential, which is a C fiber-evoked polysynaptic response and believed to reflect nociception [25].…”
Section: Effect Of Spinal Dopaminerg Ic Receptor On the Circadian Pwtmentioning
confidence: 99%
“…Nociception is a complex process integrated by the primary afferent fibers, dorsal horn of the spinal cord, ascending and descending supraspinal pathways, and higher brain centers [2,[11][12][13]. In recent years, there has been an increased interest in analyzing the descending modulatory pathways of nociception at the spinal cord, particularly noradrenergic, serotonergic, and dopaminergic fibers [2,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%